WHITEWASHING HEATHCLIFF: RACIAL ERASURE IN WUTHERING HEIGHTS ADAPTATIONS (2011, 2026) - Nasywa Salsabila Putri; Zulidyana Dwi Runalsari (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study examines the whitewashing of Heathcliff in film adaptations of Emily Brontë’s Wuthering Heights and argues that such practices constitute a form of structural racial erasure. Drawing on Critical Race Theory (CRT), adaptation theory, close reading, and Visual Discourse Analysis (VDA), the study investigates how Heathcliff’s racial identity is constructed in the novel and represented in the 2011 and 2026 film adaptations. Film adaptations play a crucial role in shaping public interpretations of literary texts, yet they often reproduce dominant racial ideologies through casting practices. The findings reveal that Heathcliff’s racial otherness is central to the narrative, shaping his experiences of exclusion, marginalization, and revenge. A review of adaptation history demonstrates a persistent pattern of whitewashing, with Andrea Arnold’s 2011 adaptation serving as a notable exception through its casting of a Black actor as Heathcliff. Comparative visual analysis further shows that the 2011 adaptation foregrounds Heathcliff’s racial identity through casting and cinematographic techniques, whereas Emerald Fennell’s 2026 adaptation minimizes racial difference and reconstructs Heathcliff as a racially unmarked romantic hero. The study concludes that the repeated erasure of Heathcliff’s racial identity reflects broader structural inequalities within the film industry and significantly alters the cultural interpretation of Brontë’s novel. By integrating CRT, close reading, and VDA, this research contributes to adaptation studies and media representation scholarship by demonstrating how racial erasure operates across literary adaptations and reinforces dominant racial narratives within contemporary visual culture.